Odpowiedź :
Odpowiedź:
[tex]\frac{8*3^4*3^{11}-9*3^{12}}{46*(3^{18}:3^4)} =\frac{8*3^{15}-3^2*3^{12}}{46*(3^{14})} =\frac{8*3^{15}-3^{14}}{46*(3^{14})} =\frac{3^{14}*(8*3-1)}{46*(3^{14})} =\frac{23}{46} =\frac{1}{2}[/tex]
Szczegółowe wyjaśnienie:
[tex]zad.f\\\\\dfrac{8\cdot 3^{4}\cdot 3^{11} -9\cdot 3^{12} }{46\cdot (3^{18} \div 3^{4} )} =\dfrac{8\cdot 3^{4+11} -9\cdot 3^{12} }{46\cdot 3^{18-4}} =\dfrac{8\cdot 3^{15} -9\cdot 3^{12} }{46\cdot 3^{14}} =\dfrac{8\cdot 3^{15} -3^{2} \cdot 3^{12} }{46\cdot 3^{14}} =[/tex]
[tex]=\dfrac{8\cdot 3^{15} -3^{2+12} }{46\cdot 3^{14} } =\dfrac{8\cdot 3^{15} -3^{14} }{46\cdot 3^{14} } =\dfrac{8\cdot 3^{14} \cdot 3^{1}-3^{14} }{46\cdot 3^{14}}=\dfrac{3^{14} (8\cdot 3 - 1 )}{3^{14}\cdot 46} =\dfrac{24-1}{46}=\dfrac{23}{46} =\dfrac{1}{2} =0,5[/tex]